Drive-Leg kinematics during the windup and pushoff is associated with pitching kinetics at later phases of the pitch - Fava, A. W.; Downs Talmage, J. L.; Plummer, H. A.; Oliver, G. D. (The American Journal of Sports Medicine, 2022)
Background: Inconsistent findings exist between drive-leg ground-reaction forces (GRFs) and pitching mechanics. Previous literature has largely reported drive-leg mechanics and GRFs at the start of the pushoff phase for their role in initiating force development. Little research has assessed drive-leg kinematics that includes a pitcher`s windup motion to determine its effects on subsequent phases in the pitching motion.